Kepemimpinan dan Tantangan Generasi di Era Digital di Gekisia Depok Berdasarkan Roma 12:2 - Bertha Cristine Zebua; Asep Afaradi (Damai : Jurnal Pendidikan Agama Kristen dan Filsafat, 2026)
Technological developments have brought significant changes to various aspects of human life, including church life. These changes also impact intergenerational relationships within the congregation. This paper aims to examine the challenges faced by church leaders at GEKISIA Depok in serving Generation X, Millennials, and Generation Z, and to examine the relevance of the theological principle of Romans 12:2 in addressing these challenges. Ultimately, the author observes that differences in generational characteristics influence communication patterns, ministry models, and congregational expectations of church leadership. Therefore, church leaders in the digital age are required to be adaptive, transformative, and remain rooted in biblical values. Romans 12:2 serves as an important theological foundation for Christian leaders to experience a renewed mindset so they can serve according to God's will without being influenced by worldly patterns. Furthermore, the challenge of cross-generational leadership is not merely practical in nature, but also theological. Each generation brings different experiences, values, and perspectives in understanding faith and spirituality. Generation X tends to value institutional stability and loyalty, while Millennials are more oriented toward authentic experience and community. Generation Z, having grown up entirely in the digital age, communicates and expresses faith in ways that differ greatly from previous generations. In this context, church leaders are called to become bridges between generations, rather than simply following trends or rigidly preserving tradition.